Sistem Informasi Rental Mobil Berbasis Web Menggunakan Laravel 11 (Studi Kasus: CV Metro Trans Christindo Bali) - Juana, I Made Esa; I Putu Mahendra Adi Wardana; I Kadek Noppi Adi Jaya (RESI : Jurnal Riset Sistem Informasi, 2025)
Manual management of transactions and administration is still commonly found in car rental companies, often leading to recording errors, limited data tracking, and operational inefficiency. CV Metro Trans Christindo Bali is one such company facing these issues. This prompted the development of a web-based information system to improve operational efficiency and effectiveness. The system was developed using the ADDIE approach, involving the stages of needs analysis, system design, and implementation using Laravel 11, PHP 8.2, and a MySQL database. The system features include booking via messaging services, vehicle data management, rental transactions, customer reviews, and operational reporting. Testing was conducted using blackbox testing with the functional testing method to ensure each feature operates according to specifications. The results showed that the system functions optimally without significant errors and is capable of improving administrative order, work efficiency, and supporting decision-making within the company.